The role of tissue-resident memory T cells as mediators for response and toxicity in immunotherapy-treated melanoma: two sides of the same coin? - Reschke, Robin Niklas; Deitert, Benjamin; Enk, Alexander; Hassel, Jessica C. (Frontiers in immunology, 2024)
Tissue-resident memory T cells (TRM cells) have become an interesting subject of study for antitumor immunity in melanoma and other solid tumors. In the initial phases of antitumor immunity, they maintain an immune equilibrium and protect against challenges with tumor cells and the formation of primary melanomas. In metastatic settings, they are a prime target cell population for immune checkpoint inhibition (ICI) because they highly express inhibitory checkpoint molecules such as PD-1, CTLA-4, or LAG-3. Once melanoma patients are treated with ICI, TRM cells residing in the tumor are reactivated and expand. Tumor killing is achieved by secreting effector molecules such as IFN-γ. However, off-target effects are also observed. Immune-related adverse events, such as those affecting barrier organs like the skin, can be mediated by ICI-induced TRM cells. Therefore, a detailed understanding of this memory T-cell type is obligatory to better guide and improve immunotherapy regimens.